2021
DOI: 10.1002/jum.15641
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Ultrasound‐Enhanced Transcorneal PHMB Delivery In Vitro

Abstract: Objective-Delivery of therapeutic agents to the cornea is a difficult task in the treatment of parasitic keratitis. In this study, we looked at using different combinations of ultrasound parameters to enhance corneal permeability to polyhexamethylene biguanide (PHMB), a clinically available ophthalmic antiparasitic formulation.Methods-Permeability of PHMB was investigated in vitro using a standard diffusion cell setup. Continuous or 25% duty-cycle ultrasound was used at frequencies of 400 or 600 kHz, intensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
(155 reference statements)
0
9
0
Order By: Relevance
“… 31 Our previous research findings indicated that ultrasound can be effective and safe for transcorneal delivery of various topically applied compounds into the eye, including the small hydrophilic drug-mimicking compound sodium fluorescein, steroid DEX sodium phosphate, anti-parasitic compound PHMB, and various antiglaucoma drugs. 35 41 In our previous transcorneal experiments, we observed up to 10 drug delivery enhancements with minimal and reversible changes in the eye tissues, as determined in short-term safety studies. Few studies have been conducted using therapeutic ultrasound to enhance sclera drug delivery.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“… 31 Our previous research findings indicated that ultrasound can be effective and safe for transcorneal delivery of various topically applied compounds into the eye, including the small hydrophilic drug-mimicking compound sodium fluorescein, steroid DEX sodium phosphate, anti-parasitic compound PHMB, and various antiglaucoma drugs. 35 41 In our previous transcorneal experiments, we observed up to 10 drug delivery enhancements with minimal and reversible changes in the eye tissues, as determined in short-term safety studies. Few studies have been conducted using therapeutic ultrasound to enhance sclera drug delivery.…”
Section: Introductionmentioning
confidence: 80%
“… 54 The unpaired t -test assuming unequal variances was used to compare the receiver compartment absorbance distribution of the sham and ultrasound groups. 35 37 , 39 41 , 55 …”
Section: Methodsmentioning
confidence: 99%
“…In other small molecule drug therapy models, US can increase the drug concentration of poly hexamethylene biguanide by up to 2.63 times and thus treat parasitic keratitis, 84 as well as using US to promote the uptake of trehalose by red blood cells, increasing the recovery of viable cells after lyophilization and rehydration, thus enabling long-term storage of blood. 85 Besides, Aryal et al found that the molecular weight of chemical drugs may not be a crucial factor for endocytosis.…”
Section: Us-enhanced Cellular Endocytosis Strategies For Biomedical A...mentioning
confidence: 99%
“…94 Ultrasound has shown promising potential as a tool to enhance drug delivery in vitro. In a recent study by Karpinecz et al, 95 dissected rabbit corneas permeabilized polyhexamethylene biguanide, an ophthalmic antiparasitic formulation, 2.5-fold better after 60 min of ultrasound exposure compared to sham eyes. These results suggest that ultrasound alone or in combination with contrast agents presents new avenues for delivering therapeutics to a wide range of ocular tissue types.…”
Section: In Vitromentioning
confidence: 99%